2008
DOI: 10.1002/ptr.2493
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic constituents from Andrographis paniculata induce cell cycle arrest in jurkat cells

Abstract: Herbal medicines are now attracting attention as potential sources of anticancer agents. Andrographis paniculata is a traditionally used anticancer herb in Indian and Chinese herbal medicine. Phytochemical investigation of the ethanol extract of the aerial parts of this herb resulted in the isolation of 14 compounds including flavonoids and labdane diterpenoids. This is the first isolation of compound 6 from a natural source, and the aerial parts of A. paniculata are a rich source for the molecule andrographol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 29 publications
2
52
1
1
Order By: Relevance
“…For therapeutic effectiveness, drugs are being developed that act as biological modifiers, regulating the cell cycle and promoting cell death [59]. Plant derived compounds have been reported to induce cell cycle arrest and cell death in many tumor cell lines [60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…For therapeutic effectiveness, drugs are being developed that act as biological modifiers, regulating the cell cycle and promoting cell death [59]. Plant derived compounds have been reported to induce cell cycle arrest and cell death in many tumor cell lines [60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic activities of these compounds have been evaluated against various cell lines and found that these isolates have a potent tumour inhibitory activity against all investigated cell lines 35 .…”
Section: Andrographis Paniculatamentioning
confidence: 99%
“…However toxicity related side effects are more common and are highly expensive and thus are far beyond reach of people who live in underdeveloped and poor countries [12][13][14]. Recent studies demonstrated that Andrographis plants particularly, A. paniculata possess anticancerous properties against several cancers [15][16][17]. However, recent studies revealed that there are side effects associated with A. paniculata that includes gastric upset, headache, bitter taste and fatigue and high concentrations of A. paniculata may disturb normal liver function.…”
Section: A Echioides (Ae) Leaf and Stem Extracts Reduce The Clonogenmentioning
confidence: 99%